2011
DOI: 10.1254/jphs.10279fp
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Cardioprotective Effects of Docetaxel Pre-administration Against Adriamycin-Induced Cardiotoxicity

Abstract: Abstract. We revealed that pre-treatment with docetaxel (DOC) 12 h before adriamycin (ADR) administration significantly reduced ADR-induced toxic death compared with the simultaneous dosing schedule that was commonly used in previous studies. We considered that pre-treatment with DOC relieves ADR-induced cardiotoxicity. In this study, we investigated the influence of DOC on the pharmacokinetics and pharmacodynamics of ADR in order to clarify the mechanism by which DOC pre-treatment relieves ADR-induced cardiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…In the present study, DOX intoxication signifi cantly decreased the duration of both QRS complex and P wave, increased the RR interval, QT interval and brought about ST segment elevation. In line with the present study, previous studies demonstrated that the duration of P wave (16) and QRS complex (1,16) decreased, while the RR interval duration (1,17,18,(19)(20) increased. P wave, QRS complex duration, and RR interval are frequently transient and no specifi city to DOX-induced toxicity can be assigned to them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, DOX intoxication signifi cantly decreased the duration of both QRS complex and P wave, increased the RR interval, QT interval and brought about ST segment elevation. In line with the present study, previous studies demonstrated that the duration of P wave (16) and QRS complex (1,16) decreased, while the RR interval duration (1,17,18,(19)(20) increased. P wave, QRS complex duration, and RR interval are frequently transient and no specifi city to DOX-induced toxicity can be assigned to them.…”
Section: Discussionsupporting
confidence: 93%
“…P wave, QRS complex duration, and RR interval are frequently transient and no specifi city to DOX-induced toxicity can be assigned to them. Many studies are in agreement with our study by reporting that QT interval prolongation and ST segment elevation brought about by DOX administration have been relatively characteristic ECG fi ndings as a result of DOX-induced cardiotoxicity (1,16,17,18,19,(20)(21). The prolongation of QT interval and ST segment elevation may be linked to the cellular membrane damage owing to oxidative stress (22,23).…”
Section: Discussionsupporting
confidence: 90%
“…Adriamycin can lead to the production of free radicals and cell oxidative damage in the body. The free radicals directly attack the membrane lipids, causing the changes in membrane structure and function 12 . The large dose of adriamycin can seriously inhibit the myocardial contractile function of rats, leading to the AHF.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our results revealed that the ST and QT intervals were significantly extended in mice exposed to free DOX in comparison with those in the control group. Several studies have shown a positive association between DOX cardiotoxicity and QT and ST-interval duration [27][28][29]. ST-interval elongation in DOX-injected mice is due to an increase in action potential duration [30].…”
Section: Ast (U/l) Alt (U/l) Ldh (U/l) Ck-mb (U/l)mentioning
confidence: 99%